GAMBARAN PERILAKU PETUGAS TERHADAP PENANGANAN SAMPAH MEDIS DI RUMAH SAKIT ISLAM IBNU SINA PADANG PANJANG TAHUN 2022 - DIA INTRI PRAMESUARI; SILVIA ADI PUTRI; HENDRY WIBOWO (LP2MTBM MAKARIOZ, 2022)
Based on initial observations made at the Ibn Sina Islamic Hospital Padang Panjang, non-medical waste was found in the medical waste container. Therefore, solid medical waste management requires further study to find solutions. The purpose of this study was to find out the description of officer behavior towards handling medical waste.This research was conducted using quantitative research methods. The population in the study were all nursing staff at Ibn Sina Islamic Hospital Padang Panjang and the number of samples in this study were 45 respondents. The data analysis technique in this study is Univariate and the data is processed using a computerized program.The results of this study indicate that 45 respondents stated knowledge 12 (26.7%) respondents with low categories and 33 (73.3%) respondents with high categories, attitudes 9 (20.0%) respondents with bad categories and 36 (80.0%) respondents with good categories, and actions 8 (17. It can be concluded that the level of knowledge of nurses on the handling of medical waste at Ibn Sina Islamic Hospital Padang Panjang from 45 respondents there were (73.3%) respondents with high knowledge categories and (26.7%) low knowledge categories. Therefore, it is expected that the hospital to increase socialization about handling medical waste.